Review of the genus Cochylidia Obraztsov (Lepidoptera: Tortricidae: Cochylini) in China - Sun, Yinghui; Li, Houhun (Zootaxa, 2012)
The species of the genus Cochylidia Obraztsov, 1956 that occur in China are reviewed. Nine species and one subspeciesare treated, including two new species, C. multispinalis Sun & Li, sp. nov., and C. liui Sun & Li, sp. nov., and three speciesnewly recorded for China, C. altivaga Diakonoff, 1976, C. contumescens (Meyrick, 1931), and C. implicitana (Wocke,1856). Cochylidia oblonga Liu & Ge, 1997 is regarded as a nomen nudum, and it is formally described herein as Cochy-lidia oblonga Liu & Ge, sp. nov. Images of adults and genitalia are provided, along with a key to all the known species of the genus.